The impact of seawater warming on fatty acid composition and nutritional quality indices of Trematomus bernacchii from the Antarctic region. - Pedro Araujo; Cristina Truzzi; Ikram Belghit; Matteo Antonucci (2021)
There is a growing interest in exploiting Antarctic fisheries for human consumption. However, information on how the nutritional qualities of these resources will respond to the predicted seawater warming in the region for the next century is poor. The present research investigates changes in various nutritional indices of dietary importance (e.g. the ratio polyunsaturated to saturated fatty acids, the atherogenicity index, the thrombogenicity index, the hypo-cholesterolemic to hyper-cholesterolemic index, the health-promoting index, the flesh lipid quality and the ratio omega-3 to omega-6 index) by determining the fatty acid composition in muscle of Trematomus bernacchii (an Antarctic fish species) in its natural habitat (-1.87 ◦C) and warmer temperatures (0.0, 1.0, 2.0 ◦C). Comparison of the estimated nutritional indices at - 1.87 ◦C with those at warmer temperatures revealed that seawater warming caused changes in the nutritional indices in the range of - 12%< 30%. The observed changes were not statistically significant and ascribed to biological variability. Therefore, the nutritional values of T. bernacchii muscle were preserved after increasing the temperature of its natural habitat by + 4 ◦C. The present research is the first report describing the nutritional quality indices for an Antarctic fish species and the consequences of seawater warming on the nutritional value of T. bernacchii.